EMPOWERING HYPERTENSIVE OLDER ADULTS THROUGH COLORING THERAPY TO REDUCE ANXIETY - Noor Rochmah Ida Ayu Trisno Putri; Etika Dewi Cahyaningrum (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2026)
Introduction: Hypertension in older adults is often accompanied by anxiety, which may worsen physical conditions and reduce quality of life. Coloring therapy, was implemented in this community service activity to reduce anxiety and improve the psychological well-being of older adults with hypertension. Methods: This community service was conducted at Posyandu Desa Ledug, involving 35 older adults hypertension who were registered at the posyandu, had good communication skills, and showed symptoms of anxiety. The aim to reduce anxiety and improve psychological well-being through coloring therapy. The implementation consisted of four phases, preparation include coordination with the local health center, assessment phase baseline blood pressure and anxiety measurement using the Geriatric Anxiety Scale (GAS), intervention phase and evaluation phase. Data were analyzed descriptively. Results: Most participants were aged 60 to 74 years (77.1%), female (85.7%), had hypertension for more than 10 years (57.1%), rarely attended check-ups, consumed antihypertensive medication (42.9%), and experienced moderate anxiety (65.7%). After  8-session coloring therapy intervention over 4 weeks, anxiety level improved. Mild anxiety increased to 57.1%, moderate anxiety decreased to 40%, and severe anxiety was found 2.9%. Conclusion: Coloring therapy had a positive effect in reducing anxiety among older adults with hypertension, shown by the increase proportion of mild anxiety and a reduce moderate and severe anxiety. This empowerment program indicates that coloring therapy can be applied as an alternative non-pharmacological intervention by healthcare providers and community health workers. KEYWORDS anxiety; community empowerment; hypertension; older people